IMPLEMENTASI PEMBERIAN DZIKIR UNTUK MENGURANGI HALUSINASI PENDENGARAN DI RSJ PROF DR. SOERJONO MAGELANG - Adi Juniarto; Ita Apriliyani (Sekolah Tinggi Pariwisata Mataram, 2023)
Auditory hallucinations are often encountered due to external stimulation, although the impact of hallucinations is actually part of the sufferer's life which still often appears in the patient's mind due to the effects of overthinking. In the case study, this research used a descriptive method with the respondent being Mr. R, one of the patients with auditory hallucinations at the Prof. Dr. psychiatric hospital. Soerojo Magelang, as well as for the implementation of Nursing that will be given to Mr. R is dhikr therapy to reduce auditory hallucinations